The Bible and Its Interpretative Communities in West Africa - Mensah, Michael Kodzo (Ghana journal of religion and theology, 2025)
The introduction of the Bible by Western Missionaries from various denominations in the pre-colonial period resulted in its sacred texts being interpreted with varying and sometimes contrasting theological emphasis. This has continued to the present day with a multiplication of interpretive strategies emerging from various Christian communities in West Africa. In addition, African Biblical scholars continue to apply varying strategies to the biblical text to facilitate the reception of its message in a way that addresses the existential questions and development aspirations of African peoples. Meanwhile, ordinary secular readers of the Bible, independent of Church and academia continue to read and apply the Bible to their socio-economic contexts unfettered by the consideration of church and academia. This study locates itself within the current conversations within African Biblical Interpretation generally and seeks to interrogate the interpretive strategies of churches, academia and lay interpreters of the Bible in West Africa. It argues that these three groups illustrate Stanley Fish’s concept of interpretive communities which shape the way culturally-centered texts are read which has implications for the reception of the Bible in West Africa.